The economic antecedents of human well being: a pooled mean group estimation of dynamic heterogeneous panel - Rasiah, R. R. V.; Habibullah, Muzafar Shah; Baharom, A. H. (American Scientific Publishers, 2015)
This study seeks to investigate the economic antecedents of happiness by employing the Mean Group (MG), Pooled Mean Group (PMG) and the Dynamic Fixed Effects (DFE) estimators to analyse a set of macro panel data on selected OECD countries for 40 years from 1973 to 2012. The results show evidence that income and unemployment have a favourable impact on happiness, while happiness is hindered by inflation and income inequality. Surprisingly, the study revealed that institutional quality is not a significant antecedent of happiness. It is worth noting the importance of the reference group theory or relative theory of happiness and the set-point theory of happiness in explaining the role played by income, unemployment, inflation, income inequality and institutional quality in explaining human well-being.